Reduced nucleotomy-induced intervertebral disc disruption through spontaneous spheroid formation by the Low Adhesive Scaffold Collagen (LASCol). (March 2020) - Takeoka, Yoshiki; Yurube, Takashi; Morimoto, Koichi; Kunii, Saori; Kanda, Yutaro; Tsujimoto, Ryu; Kawakami, Yohei; Fukase, Naomasa; Takemori, Toshiyuki; Omae, Kaoru; Kakiuchi, Yuji; Miyazaki, Shingo; et al.
Abstract: Back pain is a global health problem with a high morbidity and socioeconomic burden. Intervertebral disc herniation and degeneration are its primary cause, further associated with neurological radiculopathy, myelopathy, and paralysis. The current surgical treatment is principally discectomy, resulting in the loss of spinal movement and shock absorption. Therefore, the development of disc regenerative therapies is essential. Here we show reduced disc damage by a new collagen type I-based scaffold through actinidain hydrolysis—Low Adhesive Scaffold Collagen (LASCol)—with a high 3D spheroid-forming capability, water-solubility, and biodegradability and low antigenicity. In human disc nucleus pulposus and annulus fibrosus cells surgically obtained, time-dependent spheroid formation with increased expression of phenotypic markers and matrix components was observed on LASCol but not atelocollagen (AC). In a rat tail nucleotomy model, LASCol-injected and AC-injected discs presented relatively similar radiographic and MRI damage control; however, LASCol, distinct from AC, decelerated histological disc disruption, showing collagen type I-comprising LASCol degradation, aggrecan-positive and collagen type II-positive endogenous cell migration, and M1-polarized and also M2-polarized macrophage infiltration. Reduced nucleotomy-induced disc disruption through spontaneous spheroid formation by LASCol warrants further investigations of whether it may be an effective treatment without stem cells and/or growth factors for intervertebral disc disease.